EFEKTIVITAS PENGGUNAAN APLIKASI KONTRAKSI NYAMAN TERHADAP INTENSITAS NYERI PERSALINAN KALA I - Wijayanti, Irfana Tri; Altika, Sifa (Coping: Community of Publishing in Nursing; Vol 8 No 4 (2020): Desember 2020, 2020)
Pain in childbirth is a physiological thing, this pain is caused by the contraction and stretching of the lower uterine and cervical segments. In the active phase of labor, the fear of primigravida is higher than that of multigravidas and contributes to the level of pain and duration of labor. Along with the development of appropriate technology and the growing application of technology in life, it is necessary to create a comfortable contraction application packaged in an application on Android made to help mothers feel the comfort of giving birth and get a positive experience during childbirth. The purpose of this study was to determine the effectiveness of using a comfortable contraction application on the intensity of the first stage labor pain in Kudus Regency. This research method used an experimental design with one group pre test and post test. The sample of this research is 30 mothers who will give birth. The research instrument uses an android which includes a comfortable contraction application and a pain observation sheet. The paired T test shows the results of p value = 0.000 <0.05, which means that there is the effectiveness of the application of comfortable contractions on the first stage labor pain before and after in the intervention group. The mean value before the intervention was 5.93 ± 1.70 and after using the application the average pain decreased to 1.45 ± 1.45.